Depression, Anxiety, and Physical Activity Among Antenatal Women During Covid-19 Pandemic - Siti Roshaidai Mohd Arifin; Seri Wardah Zulkifli; Khadijah Hasanah Abang Abdullah; Fathima Begum Syed Mohideen; Nurul Ain Hidayah Abas; Asma Perveen; Rohayah Husain; Khairi Che Mat; Karimah Hanim Abd Aziz; Edre Mohamad Aidid; Ramli Musa; Izazol Idris (Intelektual Pustaka Media Utama (IPMU) in collaboration with Institute of Advanced Engineering and Science (IAES), 2024)
Indexed by SCOPUS